Concentrations of citalopram and escitalopram in postmortem hair segments. (July 2022) - Rygaard, Karen; Nielsen, Marie Katrine Klose; Linnet, Kristian; Banner, Jytte; Johansen, Sys Stybe
Abstract: Hair analysis can provide information regarding previous drug intake and use patterns, as the drugs consumed are incorporated into the hair. Therefore, reference values for drugs in hair are valuable in forensic investigations, especially when evaluating drug intake and assessing drug tolerance. The aim of the study was to determine concentrations of citalopram, escitalopram, and their primary metabolites in hair segments from deceased individuals with mental illness. Concentrations in up to six months prior to death were evaluated and compared with the estimated daily doses. Hair samples collected from 47 deceased individuals, were segmented in one to six 1 cm segments, and extracted overnight in medium. The concentrations in hair were quantified via ultra-high-performance liquid chromatography–tandem mass spectrometry. Following this quantification, the extracts were reanalyzed qualitatively using a chiral method to distinguish between citalopram and escitalopram intake. We found hair concentrations (10–90 percentile (perc.)) of citalopram from 0.12 to 67 ng/mg with a median of 8.2 ng/mg (N = 40 individuals, n = 182 segments) and of escitalopram from 0.027 to 7.0 ng/mg with a median of 3.9 ng/mg (N = 4, n = 23). The metabolite-to-drug ratios in hair (10–90 perc.) of citalopram were 0.091–0.57 with a median of 0.30 (N = 39) and of escitalopram were 0.053–0.63 with a median of 0.41 (N = 3). No correlations were found between concentrations in the hair and the estimated daily dose. However, our results indicate higher concentrations in dark hair compared to light hair, given the estimated doses, and thus an influence of hair color on the results. A significant positive correlation was found between the concentration of citalopram in the proximal segment and the blood concentrations. The median R/S-ratio of citalopram in hair was 1.5 and was similar to previously reported ratios in blood. In the present study, we report concentrations of citalopram and escitalopram in postmortem hair and their relation to an estimated daily dose and thus contribute valuable information in forensic investigations. Highlights: Citalopram hair concentrations ranged 0.0053–122 ng/mg with a median of 8.2 ng/mg. Analysis of 1 cm hair segments from deceased individuals with mental illnesses. Metabolite-to-drug and R/S -ratios of citalopram in hair were similar to blood ratio. Significant correlations between concentrations of citalopram in hair and blood. Tendency towards higher concentrations in dark hair when considering estimated dose.